Microbial community profiling of human gastrointestinal cancers - Thomas, Andrew Maltez (2018)
The human microbiome - defined as the microbial communities that live in and on our bodies - is emerging as a key factor in human diseases. The expanding research field that investigates the role of the microbiome on human cancer development, termed oncobiome, has led to important discoveries such as the role of Fusobacterium nucleatum in colorectal cancer carcinogenesis and tumor progression. Motivated by these discoveries, this thesis studied the oncobiome from different perspectives, investigating whether alterations to microbial profiles were associated with disease status or an adverse response to treatment. We used both biopsy tissue samples and 16S rRNA amplicon sequencing (N = 36), as well as privately and publicly available fecal whole metagenomes (N = 764) to investigate microbiome-colorectal cancer (CRC) associations. We observed significant increases in species richness in CRC, regardless of sample type or methodology, which was partially due to expansions of species typically from the oral cavity, as well as an overabundance of specific taxa such as Bacteroides fragilis, Fusobacterium, Desulfovibrio and Bilophila in CRC. Functional potential analysis of CRC metagenomes revealed that the choline trimethylamine-lyase (cutC) gene was over-abundant in CRC, with the strength of association dependent on four identified sequence variants, pointing at a novel potential mechanism of CRC carcinogenesis. Predictive microbiome signatures trained on the combination of multiple datasets showed very high and consistent performances on distinct cohorts (average AUC 0.83, minimum 0.81). To investigate the microbiomes role in response to treatment, we profiled microbial communities of gastric wash samples in gastric cancer patients (N = 36) before and after neoadjuvant chemotherapy through 16S rRNA amplicon sequencing. Gastric wash microbial communities presented remarkably high inter-individual variation, with significant decreases in richness and phylogenetic diversity after treatment and associations with pH, pathological response and sample collection. The most abundant genera found in patients before or after chemotherapy treatment included Streptococcus, Prevotella, Rothia and Veillonella. Despite limitations inherent to differing experimental choices, this thesis provides microbiome signatures that can be the basis for clinical prognostic tests and hypothesis-driven mechanistic studies, as well as supporting the role of the human oral microbiome in whole-body diseases.